Primary thromboprophylaxis to prevent thrombotic events in pediatric oncology patients with a malignant mediastinal mass. Issue 12 (24th September 2021) - Sarangi, Susmita N.; Gaballah, Marian; Nolfi‐Donegan, Deirdre; Battaglia, Maria; Amin, Seema; Amodio, John; Acharya, Suchitra S.
Abstract: Children with malignant mediastinal masses have increased thrombotic events (TE). Eligible subjects with malignant mediastinal masses between January 2000 and December 2017 were evaluated for TE, with 19 among 76 subjects receiving enoxaparin thromboprophylaxis. There were 13 TEs among 76 subjects for an incidence of 17.1%. Mediastinal compression directly led to TE in 9.2% of subjects who also had statistically significant superior vena cava compression at diagnosis. Primary thromboprophylaxis did not significantly affect TE occurrence; however, larger studies are warranted to consider strategic thromboprophylaxis guided by radiological monitoring of dynamic vascular compression to improve TE outcomes.